Circulating pancreatic cancer exosomal RNAs for detection of pancreatic cancer. Issue 2 (15th November 2018) - Kitagawa, Tatsuya; Taniuchi, Keisuke; Tsuboi, Makiko; Sakaguchi, Masahiko; Kohsaki, Takuhiro; Okabayashi, Takehiro; Saibara, Toshiji
Abstract : Diagnostic biomarkers for the early diagnosis of pancreatic cancer are needed to improve prognosis for this disease. The aim of this study was to investigate differences in the expression of four messenger RNAs (mRNAs: CCDC88A, ARF6, Vav3, and WASF2 ) and five small nucleolar RNAs (snoRNAs: SNORA14B, SNORA18, SNORA25, SNORA74A, and SNORD22 ) in serum of patients with pancreatic cancer and control participants for use in the diagnosis of pancreatic cancer. Results were compared with the expression of sialylated Lewis (a) blood group antigen CA19‐9, the standard clinical tumor biomarker. Reverse transcription quantitative real‐time PCR showed that all of the mRNAs and snoRNAs, except CCDC88A, were encapsulated in exosomes and secreted from cultured pancreatic cancer cells, and present in cell culture medium. In a discovery‐stage clinical study involving 27 pancreatic cancer patients and 13 controls, the area under the receiver operating characteristic curve (AUC) of two mRNAs ( WASF2 and ARF6 ) and two snoRNAs ( SNORA74A and SNORA25 ) was > 0.9 for distinguishing pancreatic cancer patients from controls; the AUC of CA19‐9 was 0.897. Comparing serum levels of WASF2, ARF6, SNORA74A, SNORA25, and CA19‐9 revealed that levels of WASF2 were the most highly correlated with the risk of pancreatic cancer. The AUCs of WASF2, ARF6, SNORA74A, and SNORA25 in serum from patients in the early stages of pancreatic cancer (stages 0, I, and IIA) were > 0.9, compared with an AUC of 0.93 for the level of CA19‐9. The results of this study suggest that WASF2, ARF6, SNORA74A, and SNORA25 may be useful tools for the early detection of pancreatic cancer. Monitoring serum levels of WASF2 mRNA may be particularly useful, as it was the most highly correlated with pancreatic cancer risk. Abstract : Specific messenger RNAs and small nucleolar RNAs encapsulated in exosomes are secreted from pancreatic cancer cells, and monitoring serum levels of the exosome‐associated RNAs may be useful for the early detection of pancreatic cancer.